Educational objectives articulated in the Bhagwad Gita (Bhartiya Knowledge Systems, 2024)
In this article, the significance of integrating the teachings of the Bhagavad Gita into education, specifically in values education, is discussed. The Bhagavad Gita stresses the importance of confronting life's challenges with courage and wisdom, as well as emphasizing the crucial role of harmonious child development. The article urges teachers to guide students towards self-discovery and to instill values that promote resilience and overall personal growth. The educational goals outlined in the Bhagavad Gita are ultimately emphasized in the article.